CRIMINALIZATION OF OBTAINED ACTIONS PERFORMED BY SAME-GENERAL COUPLES (HOMOSEXUAL) IN THE PERSPECTIVE OF CRIMINAL LAW REFORM - Ni Luh Rai Puspadewi; I Ketut Rai Setiabudhi (Lafadz Jaya Publisher, 2023)
Homosexuals are groups that have same sex sexual orientation (gay), different from people in general who are sexually oriented towards people of the opposite sex (heterosexual), resulting in sexual activity deviating from what it should be. The problem that will be discussed in this study is whether homosexuality is part of a crime according to Indonesian criminal law. The research method used in writing this research is a normative legal research method, because there is a norm void. Normative legal research is carried out by examining library materials by studying and reviewing legal principles and positive legal rules derived from library materials and legislation. The approaches used are the statutory approach, the concept approach and the comparative approach. Homosexuality is part of a criminal act according to Indonesian criminal law, but the regulation is still very limited because it only regulates same-sex sexual relations carried out by adults with minors. So it is necessary to criminalize or expand the criminal regulation of deviant acts committed by the gay community in the renewal of criminal law.